Evaluation of taxi services provision on airport terminal’s curbside for picking up passengers, Problem proposed by Globalvia - Correia, J.; Ferreira, F.; Pacheco, A.; Passos, L.; Rossetti, R.; Teodoro, F. (74th European Study Group with Industry, 2010)
Airport terminal’s curbsides are the critical interfaces between standing vehicles, moving vehicles and pedestrians. They act as the capacity buffer between the road delivery system and the airport terminal building. Their design and capacity are essential to the successful performance of any airport infrastructure and, therefore, determine the quality of passenger experience.
Keywords: Airport terminals curbsides; Portela Airport taxi service provision; “spine” parking design; capacity and performance